TINTING OF CAR GLASS: ANALYSIS OF THE CURRENT SITUATION IN UKRAINE AND THE EXPERIENCE OF OTHER COUNTRIES - Лескова, Тетяна; Матвієнко, Анастасія; Лебідь, Ганна; Харченко, Тамара; Тарасенко, Олександр (SWorldJournal, 2022)
The paper considers the issues of tinting of car glass, the allowed degree of tinting of glass, determines the percentage of drivers - violators of regulations and the causes of this phenomenon. Proposals to reduce the number of violations by drivers of